Evaluation of Extension of the Jajar Legowo System to Improving Agricultural Technology Knowledge - Hamdan, Ahmad; Agniatunnisa, Lasmi; Maulana, Zidan (Universitas Negeri Padang, 2022)
As technology develops, so many changes occur, especially in the agricultural sector, technology continues to develop but farmers' knowledge is limited so that they experience obstacles in development development. Therefore, extension activities were carried out in order to address the needs and problems that occurred, especially in meeting the needs of agricultural technology knowledge for farmer groups. The purpose of this study was to determine the evaluation of the implementation of the extension of the jajar legowo planting system in increasing knowledge of agricultural technology to farmer groups in the Sukamenak village. The method used in this research is qualitative, with data collection techniques through interviews, observation and documentation. The results showed that the implementation of agricultural extension as measured through the evaluation of the CIPP model which included context, input, process and product, showed that members of the farmer group gained knowledge and understanding of agricultural technology. With the extension activities carried out, it shows that these extension activities are quite effective in transferring knowledge to farmers so that farmers can be empowered because they gain and increase knowledge of farmers about agricultural technology